2022
DOI: 10.5194/npg-2021-36
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated hydrodynamic and machine learning models for compound flooding prediction in a data-scarce estuarine delta

Abstract: Abstract. Flood forecasting based on water level modeling is an essential non-structural measure against compound flooding over the globe. With its vulnerability increased under climate change, every coastal area became urgently needs a water level model for better flood risk management. Unfortunately, for local water management agencies in developing countries building such a model is challenging due to the limited computational resources and the scarcity of observational data. Here, we attempt to solve the i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Pontianak is one of the cities in West Kalimantan Province, Indonesia which is often affected by tidal floods, especially in the riverbank areas (BPIW, 2017;Gultom et al, 2020). Previous studies (Kuntinah et al, 2021;Sampurno et al, 2022a;Sampurno et al, 2022b) have shown that tidal flood in Pontianak often occurs during the high tide seasons from December to February. During this period, the tides reach a maximum height because affected by Asian monsoon (Kästner et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Pontianak is one of the cities in West Kalimantan Province, Indonesia which is often affected by tidal floods, especially in the riverbank areas (BPIW, 2017;Gultom et al, 2020). Previous studies (Kuntinah et al, 2021;Sampurno et al, 2022a;Sampurno et al, 2022b) have shown that tidal flood in Pontianak often occurs during the high tide seasons from December to February. During this period, the tides reach a maximum height because affected by Asian monsoon (Kästner et al, 2018).…”
Section: Introductionmentioning
confidence: 96%